Indonesia Defense Diplomacy: Papua's Problem Perspective - Panjaitan, Pangihutan; Jonni Mahroza,; Pujo Widodo, (Technium Social Sciences Journal, 2020)
This research is a lesson learned from the resolution of the Timor Leste conflict which is expected to be applied in efforts to resolve the Papua problem. On 30 August 1999 through a referendum held in East Timor. The 27th province of Indonesia was finally separated from Indonesia and obtained its official status as a member of the United Nations on May 20, 2002. Learning from the settlement approach in the Timor Leste case. So the Indonesian government must have more relevant policy formulations so that the same scenario does not repeat itself in solving the Papua problem. The qualitative method is used in this research, with a case study approach. The conclusion obtained is that the Government of Indonesia is obliged to realize policies that focus on the interests of the Papuan people as well as the Indonesian government's diplomatic efforts which firmly state that the Papua problem is a domestic problem whose intervention is a violation of Indonesian law and sovereignty and to end the pressure of internationalization on Papuan cases.